Captivity of the Crusader leaders by Artuqid Aamir Balaq Ghazi of Harput - Çelik, Sebahattin (Fırat University, 2021)
In the first quarter of the XIIth century, at a time when the influence of the Abbasid Caliphate on Islamic countries and rulers wear off, the Seljuks lost their unity and integrity and dealt with their internal affairs, there was not any stable force left that could prevent the Crusaders from terrorizing the Middle East and spreading in the Islamic lands and the security of Muslims’ lives and properties was in danger under the Crusader pressure, a leader came in sight in Harput. This leader was none other than Artuquid Aamir Balaq Ghazi of Harput who stopped the Crusader armies with his bravery, courage and intelligence and who became the fearful dream of the Crusaders by capturing the King of Jerusalem, the Count of Edessa and the Seigneur of Bira. The study, which is prepared by compiling fundamental and current sources, aims to introduce this great hero whose name, we think is not mentioned enough in Turkish history. The study sheds light on his endless struggle against the Crusaders and capturing their leaders during, to prevent them from spreading to Eastern Anatolia and his ensuring peace and order by chastening Armenians who were bandits in the al-Jazeera region and by means of preventing dangerous of the Batinis who caused strife in Aleppo.

XII. yüzyılın ilk çeyreğinde, Abbâsî Hilâfeti’nin İslâm ülkeleri ve yöneticileri üzerinde etkisinin azalıp bittiği, Selçukluların birlik ve bütünlüğünü kaybedip iç meseleleriyle uğraştığı, Haçlıların Ortadoğu’da terör estirmelerini ve İslâm topraklarında yayılmalarını önleyebilecek istikrarlı bir kuvvetin kalmadığı, Müslümanların Haçlı baskısı altında can ve mal güvenliklerinin tehlike altında olduğu bir dönemde Harput’ta bir lider ortaya çıktı. Bu lider, yiğitliği, cesareti ve akıllılığı ile Haçlı ordularını durduran; Kudüs kralı, Urfa kontu ve Birecik senyörünü tutsak ederek Haçlıların korkulu rüyası haline gelen Harput Artuklu Emîri Belek Gazi’den başkası değildi. Temel ve güncel kaynakların derlenmesi suretiyle hazırlanan çalışmada, Türk tarihinde yeterince adından söz edilmediğini düşündüğümüz bu büyük kahramanı tanıtmak amaçlanmış, onun Haçlılara karşı bitmek tükenmek bilmeyen mücadelesi esnasında Haçlı liderlerini tutsak alması, Doğu Anadolu’ya doğru yayılmalarını önlemesi, el-Cezire bölgesinde eşkıyalık yapan Ermeniler ile Halep’te fitneye sebep olan Bâtınîler tehlikesini önlemek suretiyle huzur ve asayişi temin etmesine yer verilmiştir.
HARPUT ARTUKLU EMÎRİ BELEK GAZİ’NİN HAÇLI LİDERLERİNİ TUTSAK ETMESİ